2002
DOI: 10.1128/aem.68.12.5804-5815.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulfoniopropionate: Its Sources, Role in the Marine Food Web, and Biological Degradation to Dimethylsulfide

Abstract: The massive quantities of phytoplankton in the North Atlantic and Antarctic oceans producing dimethylsulfoniopropionate (DMSP) as an osmoprotectant, much of which is degraded by marine bacteria to dimethylsulfide (DMS), ensures an important role for both compounds in the global sulfur cycle. The closest to a comprehensive review on this topic is a book of symposium proceedings edited by Kiene et al. (75); the more recent developments related specifically to DMSP degradation by microbial communities are found e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
365
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(380 citation statements)
references
References 141 publications
(191 reference statements)
10
365
3
2
Order By: Relevance
“…An increase in host caspase 3-like activity (a measure of the initiation of a cell death response) was however recorded in P. damicornis at the lowest salinity (H (2) ¼ 8.867, p ¼ 0.01, electronic supplementary material, figure S1i). Freshwater dilutions resulted in altered seawater carbonate chemistry, with a significant decrease in total alkalinity (H (2) figure 2a; dark grey bars), whereas no statistical difference or change was detected in S. pistillata or P. damicornis (figure 2b,c). Host glutathione (GS x ) increased with decreasing salinity in all three species (A. millepora H (2) ¼ 11.17, p ¼ ,0.001, figure 3a; light grey bars, S. pistillata H (2) ¼ 10.67, p ¼ ,0.001, figure 3b and figure 3c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in host caspase 3-like activity (a measure of the initiation of a cell death response) was however recorded in P. damicornis at the lowest salinity (H (2) ¼ 8.867, p ¼ 0.01, electronic supplementary material, figure S1i). Freshwater dilutions resulted in altered seawater carbonate chemistry, with a significant decrease in total alkalinity (H (2) figure 2a; dark grey bars), whereas no statistical difference or change was detected in S. pistillata or P. damicornis (figure 2b,c). Host glutathione (GS x ) increased with decreasing salinity in all three species (A. millepora H (2) ¼ 11.17, p ¼ ,0.001, figure 3a; light grey bars, S. pistillata H (2) ¼ 10.67, p ¼ ,0.001, figure 3b and figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…Dimethylsulfoniopropionate (DMSP) represents a major fraction of organic sulfur within marine systems [1,2] and is produced by many macroalgae and microalgal species, including dinoflagellates from the genus Symbiodinium. Scleractinian or reef-building corals, which comprise a symbiosis between an animal host (Cnidarian phylum) and a symbiotic dinoflagellate algae (Symbiodinium), are among the largest producers of DMSP [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Both the DMSP demethylation and cleavage pathways yield a C3 compound, possibly acrylate (Kiene and Linn, 2000b), although recent studies suggest that acryloyl-CoA or 3-OH-propionate can also be intermediates (Curson et al, 2008;Todd et al, 2010). Studies of marine and freshwater isolates have shown that some bacteria can grow on acrylate by conversion to 3-OH-propionate (Kiene, 1990;Ansede et al, 1999Ansede et al, , 2001Yoch, 2002). The pattern of transcript enrichment after DMSP addition suggests that the most common degradation pathway of the C3 moiety of DMSP is to acetyl-CoA by malonyl-CoA (Figure 2, see abundances of propanoate-related transcripts in Supplementary Table S5), although this is likely to be taxon-dependent and possibly temporally variable.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, DMSP can be cleaved to produce DMS and a C3 compound (Kiene and Linn, 2000b;Todd et al, 2007). Cultured bacteria that are able to carry out both pathways have been described Yoch, 2002), and assimilation of the sulfur moiety appears to be a widespread capability in natural bacterial communities (Yoch, 2002;Malmstrom et al, 2004a;Vila-Costa et al, 2007). However, for most bacterial transformations involved in DMSP degradation, the identity of the main bacterial groups, and the factors controlling the biological switch between DMSP pathways, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…When released from such organisms, other marine microbes can use several wholly different ways to catabolize DMSP (Yoch, 2002;Johnston et al, 2007;Howard et al, 2008). Worldwide, these biotransformations annually turn over B10 9 tons of DMSP.…”
mentioning
confidence: 99%